Radiation Effects in MgO: Mn2+ Crystals: An Experimental Analysis - Meri Abramishvili; Zaira Akhvlediani; Makvala Galustashvili; Guram Dekanozishvili; Tamaz Kalabegishvili; Vakhtang Kvatchadze; Valery Tavkhelidze (Fundamental Research and Application of Physical Science Vol. 9, 2023)
This chapter is dealing with the detection and investigation of such and similar peculiarities of radiation effects in Mg0:Mn2+ crystals. Magnesium oxide has long been of interest for various important phenomena, including such as; defect induced magnetism, spin electron reflectivity, broad laser emission, thermoluminescent dosimetry etc [1-5]. Moreover, nanostructures of this material exhibited suitability for different kinds of applications ranging from wastewater treatment to spintronics depending upon their shape and size. In that work the thermally stimulated luminescence and IR absorption spectra of Mg0:Mn2+ crystals irradiated in different reactors have been studied. The steady increase of peaks at 450 K (curve 2) and at 550 K (curve 1) is observed up to the dose of [10]15 n/cm^2 and not until relatively high fluencies their complicated non-steady behavior is registered. The trend of these changes in the same fluence range (1014 - 1017n/cm2) depends both on the initial state of the crystal and on the irradiation source, which may be explained by the "small dose effect". Such trend of the processes in the irradiated MgO: Mn(2+) crystal i.e. destruction of hole-type trapping centers at the starting stage of the irradiation, is confirmed by dependence of the absorption coefficient peak of IR bands at 3290,3370 and 1600 cm] -1 on the neutron fluence